The holistic enterprise management approach: including labor migration into modeling the dynamics of the influence factors on functioning - Kotlyarevskyy, Yaroslav; Senkivskyy, Vsevolod; Pikh, Iryna; Shyra, Taras; Kudriashova, Alona; Berest, Ihor; Shtangret, Andriy (Frontiers in Political Science, 2025)
Today, enterprise management at all levels is focused on achieving specific goals, in particular by quickly responding to any deviations in the established indicators in order to eliminate the problem by making adequate decisions. In conditions of maximum imbalance of the economic situation in the country, which, for example, is a consequence of the latest pandemic, climate or military force majeures, the existing experience has limited effectiveness in application with regard to sustainability and inclusiveness of entities functioning. The reason is the need for a deeper understanding of the nature of the influence of a wide range of factors that will determine the further methodologically grounded and accountable course of achieving goals. The basis for a more adapted approach to management can be created by holism, which today has gone beyond the scope of a philosophical concept and practical approach in life and social sciences. The main advantage of holistic enterprise management is a generalized systematic vision of all internal and external processes, in particular, based on consideration of the different nature of the impact of the main factors. The study is based on the implications assessment related to data from the Ukrainian environment, due to the simultaneous deployment of several critical macro- and microlevel factors over demography and labor migration correspondingly. Thus, a unique situation has been created that allows testing new developments for the purpose of further improving the principles of enterprise management in other countries.